Electrically chargeable inorganic persistent luminescence in an alternating current driven electroluminescent device - Cunjian Lin; Rujun Yang; Zishuang Wu; Yajing Wang; Chenhan Zhan; Hirohisa Miyata; Xiankan Zeng; Yuantian Zheng; Shihai You; Ying Lv; Yixi Zhuang; Rong-Jun Xie; et al. (Communications Materials)
Abstract Persistent luminescence (PersL) in inorganic materials, lasting from seconds to even days, has attracted considerable attention. Despite the promise of electric power-driven PersL for lighting and display device applications due to its convenience and manageability, studies on electrically driven inorganic PersL are lacking. Here, we report an inorganic PersL in electroluminescent devices, which shows an energy storage effect that persists beyond 24 h after charging with an alternating current electric field at 250 K. The spin-coating method-prepared emission layer composites consist of a small bandgap copper-doped zinc sulfide core, a high dielectric constant alumina shell and a chemically passivated dielectric polydimethylsiloxane medium (ZnS:Cu@AlOx@PDMS), and these composites exhibit well-distributed electric fields and excellent operational stability. Thermoluminescence characterization reveal that PersL with an ~ 0.3 eV trap depth in electroluminescent devices mainly arises from the charge separation via hot-electron impact excitation and charge trapping within trap states in the emission layer. This study on electrically chargeable PersL in alternating current-driven electroluminescent devices can enhance our understanding of luminescence mechanisms in inorganic semiconductors.